Grape pomace in ewes diet: Effects on meat quality and the fatty acid profile of their suckling lambs. (November 2018) - Gómez-Cortés, P.; Guerra-Rivas, C.; Gallardo, B.; Lavín, P.; Mantecón, A.R.; de la Fuente, M.A.; Manso, T.
Abstract: Grape pomace (GP) is an inexpensive natural antioxidant promising as animal feed supplement due to its high content of phenolic compounds. In order to evaluate its effect in lactating ewe rations on meat quality and fat composition of their suckling lambs, 48 Churra ewes were divided into 4 treatments. All animals were fed a ration containing linseed oil (Control) supplemented with Vitamin E or two levels of GP. Lambs were nourished exclusively by suckling until they were slaughtered. Dietary GP did not generate adverse effects on carcasses or lambs meat quality when compared with Control or Vit-E diets. GP improved the water holding capacity of the meat. In addition, lambs meat FA profile was not nutritionally affected with the diets assayed. Hence, the use of GP as a dietary supplement in ewe rations would not have negative effects on meat from suckling lambs. Graphical abstract: Highlights: Grape pomace (GP) rich in natural antioxidant was included in lactating ewe diet. Meat quality and fatty acid composition of their suckling lambs were evaluated. Dietary GP did not generate adverse effects on carcasses or lambs meat quality. GP improved the water holding capacity of the meat and fat profile was not affected.